2014
DOI: 10.1002/2327-6924.12118
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in middle-aged men with obstructive sleep apnea: State of the science

Abstract: Purpose This article presents the state of the science of anxiety in middle‐aged men with obstructive sleep apnea (OSA). OSA affects 10% of men in this population. Psychological outcomes, especially anxiety, have a significant impact on quality of life, yet are essentially ignored. Data sources Search of CINAHL, MEDLINE, PsycINFO, and PsycARTICLES, with the key words “sleep apnea” and “anxiety” and with age and gender limits, resulted in 107 articles. Based on established inclusion criteria, 71 studies were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(118 reference statements)
2
12
0
Order By: Relevance
“…29 Earlier studies have shown that stress initiates and aggravates tissue inflammation. [12][13][14][15][21][22][23][24][25][26][27][28][29][30] Elevated serum levels of cortisol and CRP found in all the patients in this study replicated the finding of previous studies. [6][7][8] Upper airway endoscopy of the entire study sample of 30 patients revealed the presence of a specific co-morbidity of upper airway inflammation, as reported by others in the past.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…29 Earlier studies have shown that stress initiates and aggravates tissue inflammation. [12][13][14][15][21][22][23][24][25][26][27][28][29][30] Elevated serum levels of cortisol and CRP found in all the patients in this study replicated the finding of previous studies. [6][7][8] Upper airway endoscopy of the entire study sample of 30 patients revealed the presence of a specific co-morbidity of upper airway inflammation, as reported by others in the past.…”
Section: Discussionsupporting
confidence: 83%
“…Chronic stress, along with hypoxic stress (due to recurrent hypoxia), further aggravates tissue inflammation. Upper airway inflammation and constriction may contribute to OSA …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to the CPAP therapy can offer significant results and improve a patient's psychosocial health. 84 In OSA patients, cognitive symptoms especially mood symptoms greatly improve after treatment with CPAP therapy. 13 In OSA patients, treatment adherence is very important.…”
Section: Psychosocial Healthmentioning
confidence: 99%
“…These factors were usually studied as predictors of CPAP adherence (Budhiraja et al, 2007;Poulet et al, 2009;Ye et al, 2012). In state of the science reviews conducted by Saunamaki and Jehkonen (2007) and more recently by the author (Shapiro, 2014), anxiety was found to be common among those with OSA. OSA symptoms have been shown to be predictors of anxiety in a population-based sample (Shapiro, Culp, & Chertok, 2014).…”
Section: Methodological: Quantitativementioning
confidence: 99%